Liberalism and Newliberalism : Liberalism in Indonesia 1999-2013 - Ahmad Shodik; Miftahuddin Miftahuddin (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2021)
The Indonesian state is authentically a country that is abundant in terms of its natural resources (SDA). The islands from Sabang to Marauke are lined with abundant and varied wealth. Starting from gold, silver, spices and so on. However, the poor state of Indonesia at this time then raises a question mark, why are Indonesia's natural resource assets which spill over cannot support the benefit of the country, instead being followed by bitterness? This problem is very complex and must be searched for causes and solutions found. The goal is so that the Indonesian state does not go bankrupt and become a country that runs aground. Indonesia is entangled in the wave of globalization which is pulling slowly into the valley of destruction. Globalization is sown through these agencies using "nirvana" propaganda for the newly developing countries, including Indonesia. Because, in principle, globalization is nothing more than a camouflage for the expansion of international capitalism which always creates new targets. The collapse caused by the scour of globalization is a historical crisis of authority and extortion of one state to another. One of the fruits of the squeezing of economic globalization is that many laws have a neoliberal flavor. It is clear that the law provides space for international companies to participate in making a profit in Indonesia. Starting from 1999-2012, there were at least 39 laws that led to liberalization. One of the effects of the direction of opening up to foreign capital is that it dominates the agricultural sector. In 2011, foreign investment was dominated by 4 countries: Singapore, the United States, Japan and the UK, covering mining, electricity, gas, water, transportation and agriculture.